Melatonin Recent Updates - Gelen, Volkan; Şengül, Emin; Kükürt, Abdulsamed (IntechOpen, 2022)
Melatonin is a powerful hormone and antioxidant with numerous effects on metabolism and human health. Available as a dietary supplement for many years, it is one of the most popular over-the-counter alternative medicines available. Featuring contributions from researchers investigating the role of melatonin in various diseases and physiological conditions, this comprehensive book offers a wide range of expert reviews on the synthesis, regulation, and physiological effects of melatonin as well as its role in various diseases.